Strengthening nationalism and love of homeland in the global era through citizenship education as national defense education - Ali, Yusuf Faisal (Universitas Negeri Yogyakarta, 2022)
This study was to find out how to strengthen nationalism and love for the homeland in the global era through citizenship education as state defense education at STKIP Pasundan, Cimahi, West Java, Indonesia. This study used descriptive case study method, where data were obtained through interview, observation, and documentation studies in the field. The results showed that the strengthening of nationalism and love for the homeland in the global era through Citizenship Education as state defense education at STKIP Pasundan, Cimahi has been going well, proven by students' awareness on nationalism and love for the homeland. In addition, through citizenship education courses, students were inhibited in strengthening nationalism and love for the homeland in the global era. This study could conclude that strengthening nationalism and love for the homeland in the global era through Citizenship Education as state defense education as to minimize behavior that did not reflect love for the homeland in the global era. Besides, the process of defending the country through Citizenship Education requires continuous effort.